Can you please check on more good that looks like you took a picture on the fridge and toaster
Your dearest friend donald trump
-5x = x + 6(1-x)
-5x = x + 6(1) + 6(-x)
-5x = x + 6 -6x
-5x = x - 6x + 6
-5x = -5x + 6
-5x + 5x = 6
0 = 6 Not equal. No solution.
(2x-5)² = (2x-1)(2x+1) -10(2x-1)
(2x-5)(2x-5) = (2x-1)(2x+1) - 20x + 10
2x(2x-5)-5(2x-5) = 2x(2x+1)-1(2x+1) - 20x + 10
4x² - 10x -10x + 25 = 4x² + 2x - 2x -1 - 20x + 10
4x² - 20x + 25 = 4x² - 20x - 1 + 10
4x² - 20x + 25 = 4x² - 20x - 9
Not equal. No solution.
Answer: i am not sure but thanks for the points have a good day
Step-by-step explanation:
-78
Step-by-step explanation:
(7-8)(78)
(-1)(78)=-78
Answer:
a^2 + b^2 = c^2
Step-by-step explanation:
a^2 + b^2 = c^2